Zad 1. Opuść nawiasy i zredukuj wyrazy podobne: a) (5x+3y+5)-(12x–9y+33)=1 b) 5x+7)+(3x – 4y + 8) = c) 6a - (2a+ 55-8) +4b = d) 5(2x+4y) -6(3x–57)+4(x - 6y) +15 = e) (4x-5 y + 3) - (15x+6y +35)= +) (4x+6y) + (2x-8y +10)= g) 4a (5a +36-6)+2b = h) 3(4x + 2y) - 5(4x – 3y) + 2(x-7y)+12 = ​

Odpowiedź :

[tex]a)\\(5x+3y+5)-(12x-9y+33)=1\\5x+3y+5-12x+9y-33=1\\5x-12x+3y+9y=1-5+33\\-7x+12y=29[/tex]

[tex]b)\\(5x+7)+(3x-4y+8)=5x+7+3x-4y+8=8x-4y+15[/tex]

[tex]c)\\6a-(2a+55-8)+4b=6a-2a-55+8+4b=4a+4b-47\\[/tex]

[tex]d)\\5(2x+4y)-6(3x-57)+4(x-6y)+15=10x+20y-18x+342+4x-24y+15=-4x-4y+357[/tex]

[tex]e)\\(4x-5y+3)-(15x+6y+35)=4x-5y+3-15x-6y-35=-11x-11y-32[/tex]

[tex]f)\\(4x+6y)+(2x-8y+10)=4x+6y+2x-8y+10=6x-2y+10[/tex]

[tex]g)\\4a(5a+36-6)+2b=4a(5a+30)+2b=20a^2+120a+2b[/tex]

[tex]h)\\3(4x+2y)-5(4x-3y)+2(x-7y)+12=12x+6y-20x+15y+2x-14y+12=-6x+7y+12[/tex]